2017
DOI: 10.1121/1.4980143
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual evaluation of violins: A psycholinguistic analysis of preference verbal descriptions by experienced musicians

Abstract: sounds and feels, and consequently conceptualization structures, rely on the variations in style and expertise of different violinists, the broader semantic categories emerging from sensory descriptions remain common across performers with diverse musical profiles, reflecting a shared perception of physical parameter patterns that allowed us to develop a musician-driven framework for understanding how the dynamic behavior of a violin might relate to its perceived quality. Implications for timbre perception and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 30 publications
0
41
0
1
Order By: Relevance
“…Music fruition and performance therefore present a well-defined framework in which to study basic psychophysical, perceptual, and biomechanical aspects of touch and proprioception, all of which may inform the design of novel haptic musical devices. There is now a growing body of scientific studies of music performance and perception from which to inform research in musical haptics, including topics and methods from the fields of psychophysics [19], biomechanics [11], music education [29], psycholinguistics [32], and artificial intelligence [20].…”
mentioning
confidence: 99%
“…Music fruition and performance therefore present a well-defined framework in which to study basic psychophysical, perceptual, and biomechanical aspects of touch and proprioception, all of which may inform the design of novel haptic musical devices. There is now a growing body of scientific studies of music performance and perception from which to inform research in musical haptics, including topics and methods from the fields of psychophysics [19], biomechanics [11], music education [29], psycholinguistics [32], and artificial intelligence [20].…”
mentioning
confidence: 99%
“…Previous studies relating auditory cues to geometry and material properties of vibrating objects have pointed out the importance of internal friction related to the damping factors of the spectral components (Avanzini and Rocchesso 2001;Giordano and McAdams 2006;Lutfi and Oh 1997;Ystad et al, SHAR 69, 2019, https://doi.org/10.1007/978-3-030-14832-4_13 Klatzky et al 2000;McAdams et al 2004McAdams et al , 2010 as theoretically shown by Wildes and Richards (1988). Other studies on sound quality of musical instruments have been performed for instance in the case of violin sounds (Saitis et al 2012(Saitis et al , 2017 based on psycholinguistic analyses of verbal descriptions from experienced musicians. These studies, based on the musician's spontaneous verbalizations describing the playing experience, led to a model linking auditory and haptic sensations to timbre, quality and playability of the instrument.…”
Section: Timbre-based Wood Selection Made By a Xylophone Makermentioning
confidence: 99%
“…A different approach relies on cognitive categories emerging from psycholinguistically inferred semantic relations in free verbalizations of sound qualities. Such analyses have provided additional insight regarding particular factors that contribute to the salient semantic dimensions of timbre [6][7][8]. Still, both semantic differential scales and free verbalization tasks seem to miss an important point: sensory nonauditory attributes of timbre exemplify a more ubiquitous aspect of human cognition known as crossmodal correspondences: people tend to map between sensory experiences in different modalities (e.g., between color and touch [9]) or within the same modality (e.g., between pitch, timbre, and loudness [10]).…”
Section: Motivationmentioning
confidence: 99%